Punishment in the public goods game is evaluated negatively irrespective of non-cooperators’ motivation - Li, Yang; Mifune, Nobuhiro (Frontiers in Psychology, 2023)
The evolution of human cooperation toward strangers remains puzzling. While the punishment of non-cooperators is a possible explanation, whether punishments can help cooperation evolve depends on how people evaluate punishers. Thus, it is of vital importance to elucidate the perception of punishers. Previous studies have found that punishment is evaluated differently in different contexts; punishers are negatively and positively evaluated in the public goods game with punishment (PGG-P) and in the third-party punishment game (TPP), respectively. To disentangle the mixed evidence, our research focused on motivations for non-cooperation and examined whether different motivations for non-cooperation could explain the inconsistent findings. We hypothesized that people positively evaluate punishers when they punish those who non-cooperated to exploit others (greed), e.g., in a TPP situation. Contrastingly, people negatively evaluate punishers when they punish those who non-cooperated to avoid exploitation (fear), e.g., in a PGG-P situation. If so, in either game, punishers would be evaluated positively in situations where greed dominates, and negatively in situations where fear dominates the non-cooperation motivation. To test this, we conducted two online experiments with hypothetical scenarios in which the decision-making order was used to manipulate the motivations of non-cooperators. The results of Study 1 (N = 240) using only PGG-P and Study 2 (N = 602) using both PGG-P and TPP showed that the non-cooperation motivation did not have a significant effect on the evaluations of punishers and non-punishers. Punishers (vs non-punishers) were evaluated negatively in PGG-P and positively in TPP regardless of the decision-making order of non-cooperation. We discussed the role of higher-order information in the evaluation of punishment.